If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9(2+y)-3y+8=-2(4y+5)
We simplify the equation to the form, which is simple to understand
-9(2+y)-3y+8=-2(4y+5)
Reorder the terms in parentheses
+(-18-9y)-3y+8=-2*(4y+5)
Remove unnecessary parentheses
-18-9y-3y+8=-2+*(+4y+5+)
Reorder the terms in parentheses
-18-9y-3y+8=+(-8y-10)
Remove unnecessary parentheses
-18-9y-3y+8=-8y-10
We move all terms containing y to the left and all other terms to the right.
-9y-3y+8y=-10+18-8
We simplify left and right side of the equation.
-4y=0
We divide both sides of the equation by -4 to get y.
y=-0
| 3x-2=10x-15 | | 9x+4x=-3 | | 1/3x-2=5 | | 4(u-10)=2(u+10) | | 12x=8-4(x+2) | | 4-x+7x=4 | | 20=4-2z | | 6x^3+8x+2=0 | | 4x-5=35+2(2x-15) | | -7-x+7x=4 | | 5/6d=d+6/5 | | 60=-16t^2+75+0 | | 2p=4480 | | 3x-2(1-2x)=0,5(3x+1,5) | | x/10=5/2 | | (4/a)*(a/16) | | 0.5-k=-2.8(2k-1.5) | | (0.3+2x)(0.6+2x)=6.02598 | | 7x+6=6x+6 | | I/2=312 | | -16/15=0 | | 6x-16=-4x+6 | | 31=-6w+1 | | 2h=482 | | d-2=14 | | h=-16t^2+4t+5 | | 7x+15=15-3x | | (16/x^2)*(x^2/24) | | -11=-5x | | x/6-8=-14 | | 2=6x-3y | | 2x+10=3x+15 |